Bacterial vaginosis modifies the association between hormonal contraception and HIV acquisition. (13th March 2018) - Haddad, Lisa B.; Wall, Kristin M.; Kilembe, William; Vwalika, Bellington; Khu, Naw H.; Brill, Ilene; Chomba, Elwyn; Tichacek, Amanda; Allen, Susan
Abstract : Objective: To examine bacterial vaginosis as an effect modifier for the association between hormonal contraception and incident HIV infection. Design: Serodiscordant couples enrolled in an open longitudinal cohort in Lusaka, Zambia from 1994 to 2012. This analysis was restricted to couples with an HIV-positive man enrolled between1994 and 2002 when a quarterly genital tract examination and HIV testing was performed. Methods: Multivariate Cox models evaluated the association between contraceptive method and HIV-acquisition, stratified by time-varying bacterial vaginosis status. Results: Among 564 couples contributing 1137.2 couple-years of observation, bacterial vaginosis was detected at 15.5% of study visits. Twenty-two of 106 seroconversions occurred during intervals after bacterial vaginosis was detected [12 on no method/nonhormonal method (nonhormonal contraception), two on injectables, eight on oral contraceptive pills (OCPs)]. Unadjusted seroincidence rates per 100 couple-years for nonhormonal contraception, injectable, and OCP users, respectively, during intervals with bacterial vaginosis were 8.3, 20.8, and 31.0 and during intervals without bacterial vaginosis were 8.2, 9.7, and 12.3. In the bacterial vaginosis-positive model, there was a significant increase in incident HIV among those using injectables (adjusted hazard ratio, aHR 6.55, 95% CI 1.14–37.77) and OCPs (aHR 5.20, 95% CI 1.68–16.06) compared with nonhormonal contraception. Hormonal contraception did not increase the hazard of HIV acquisition in bacterial vaginosis-negative models. These findings persisted in sensitivity analyses whenever all covariates from the nonstratified model previously published were included, whenever other genital tract findings were excluded from the model and with the addition of condom-less sex and sperm on wet-prep. Conclusion: Future research should consider a potential interaction with bacterial vaginosis whenever evaluating the impact of hormonal contraception on HIV acquisition.